“It’s like having a library, and you don’t get to go”: educators negotiating boundaries when working with new literacies - Seglem, Robyn L. (Kansas State University, 2009)
Historically, advances in technology have impacted education, particularly in the field of literacy. Often, educators initially resist these changes. Today, this is the case with the new literacies. Although students increasingly turn to technology to communicate, school practices still largely ignore this cultural phenomenon. This qualitative study explores the roots of this resistance by examining how teachers negotiate the use of digital literacies in the classroom, particularly in respect to the rhetorical boundaries imposed upon schools by their local culture. Data were collected through 34 interviews with individuals in three demographically different schools districts. Of particular interest were the key literacy decision makers. At the district level, assistant superintendents who also served as secondary curriculum directors, technology directors and literacy coaches were interviewed. The school level focused on middle and high schools, and, in two districts, on alternative education centers. Principals, librarian, lead English teachers and new English teachers, defined as teaching for three years or less, provided information for the study at these schools. During the data analysis, grounded theory, as well as the gap and continuum theories described by Deanna Bogdan (1992a & b), guided the study. When examining what factors create the boundaries educators work within, nine initial themes emerged: infractions, distractions, dependency, immediacy, misinformation, safety, inappropriateness, funding and change. Further examination of the data revealed the central phenomenon: “The technological evolution that occurs outside the classroom must be adapted before it makes its way into pedagogical practice.” This phenomenon provides the first layer for the model. To better understand the adaptation process, the gap and continuum theories were employed, leading to a spectrum between gatekeepers and facilitators. Each of the three districts fit in distinctively different places on this spectrum. Axial coding was then used to further explore the relationship of the themes to the adaptation process. The nine themes could then be collapsed into three categories: perceptions of student behaviors, perceptions of technology, and perception of school’s role in society. This study provides educators insight into the factors that guide their decision-making processes when considering the incorporation of technology into the classroom.
Keywords: New literacies; Technology in education; Censorship; Education, Reading (0535); Education, Technology (0710)